2013
DOI: 10.1071/he12905
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the evaluation of the Stephanie Alexander Kitchen Garden program

Abstract: The SAKG evaluation methodology will address the need for appropriate evaluation approaches for school-based kitchen garden programs. It demonstrates the feasibility of a meaningful, comprehensive evaluation of school-based programs and also demonstrates the central role qualitative methods can have in a mixed-method evaluation. So what? This paper contributes to debate about appropriate evaluation approaches to meet the information needs of all stakeholders and will support the sharing of measures and potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…This suggestion is supported within existing community garden literature [3, 37, 46, 73]. Other scholars have reiterated the point that long term and larger scale study designs are required [50, 74]. Surls [75] mentioned this needs to involve action research with more consistent research protocols, data gathering and analysis processes so that community gardening research can be compared and contrasted.…”
Section: Discussionmentioning
confidence: 88%
“…This suggestion is supported within existing community garden literature [3, 37, 46, 73]. Other scholars have reiterated the point that long term and larger scale study designs are required [50, 74]. Surls [75] mentioned this needs to involve action research with more consistent research protocols, data gathering and analysis processes so that community gardening research can be compared and contrasted.…”
Section: Discussionmentioning
confidence: 88%
“…This paper reports on the findings arising from the qualitative data component of a mixed methods research project conducted between 2006 and 2009. A description of the full project and its methods can be found in Gibbs et al (2012). At the time the project began, a total of 22 primary schools were involved in the SAKG program.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evaluations of school garden projects in Melbourne (Gibbs et al 2009) and the USA (Virginia Tech University 2003) have indicated promising results. These studies are discussed more thoroughly in section 5.5.8.…”
Section: Birch 1993 P 88mentioning
confidence: 99%